RISK OF RICE AGROINDUSTRY BASED ON SUPPLY CHAIN - Yuli Purbaningsih; Helviani Helviani; Nursalam Nursalam (International Journal of Economy, Education and Entrepreneurship, 2023)
This study aimed to identify all possible risks faced by the rice agroindustry in Kolaka Regency regarding the supply chain system. This study was a descriptive type of agroindustry in Kolaka. The results of this study were the risks faced by the rice agroindustry in terms of the supply chain and found several sources of risk factors that impact business risk. The supply chain system in the rice agroindustry consisted of 2 groups: the flow of suppliers of raw materials (grain) and the flow of product distribution (rice). The flow of raw material suppliers (grain) was dominated by grain collectors, with a market share of 60% of the total volume of yearly purchases. Meanwhile, wholesalers dominate the distribution of products (rice) and have a share of 65% of the total annual sales volume. Supply chain flows resulted in potential business risks. Identifying sources of business risk in the rice agroindustry was in the supply/procurement, transportation, storage, and processing of raw materials